The Methodology for the Evaluation of Youth Economic Potential: Revealing the Resources for Regional Development - CHERNOVA, Olga; MATVEEVA, Ludmila; MIKHALKINA, Elena (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
Among the goals of strategic development in Russia and its regions the main one to be mentioned refers to the task of reaching the trajectory of breakthrough economic growth on an innovative basis. Following this discussion, the goal of the paper is to formulate theoretical and methodological approaches, concepts and tools for assessing the condition and goal-oriented basis of the economic potential of young people as a strategic resource for the regional development. The research provides a conceptual and terminological representation of the multicomponent category ‘the economic potential of the youth of the region’. It also describes a conceptual model of its structural and functional composition and develops and verifies the methods of element-by-element assessment of their potential in the context of achieving tactical and strategic goals of regional development. Finally, the paper proposes the options or creating a roadmap in order to increase the economic activity of young people and a strategic map for the implementation of youth policy in the region from the standpoint of strategic goal-setting.